Analisis kualitas pelayanan pada PT Perusahaan Gas Negara tbk, area Karawang - Septarini, Agnes Dini; Tuhagana, Aji; Anggela, Flora Patricia (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study is to conduct an investigation into the level of service provided by PT. Perusahaan Gas Negara Tbk in the Karawang Area. Participants in this study include both employees and customers. This study employs qualitative research methods that are descriptive. Research focuses on five aspects of Prasuraman's theory: responsiveness (responsiveness), assurance (assurance), tangibility (physical), empathy (empathy), and reliability (reliability). These five aspects are listed as follows: responsiveness, assurance, tangible (physical), empathy (empathy), and reliability (reliability). The data collection method consisted of three stages, which were observation, interviews, and documentation of the results of the interviews. There are obstacles in the Responsiveness dimension, specifically in responding to messages from the community through WhatsApp services, and there are obstacles in the Physical Evidence dimension, specifically in the facility of interference, according to the findings of research related to the five dimensions of service quality. The dimensions of Assurance, Empathy, and Responsiveness all fall into the good category. increased gas pressure, which results in the gas being unstable. The findings of this research provide information that can be used by PT. Perusahaan Gas Negara Tbk, Karawang Area in terms of the quality of service on what dimensions ought to be evaluated so that it can be improved.